Feasibility of direct cryobiopsy specimen retrieval through the working channel of an ultrathin bronchoscope—a retrospective study of single institute - Takigawa, Yuki; Sato, Ken; Goda, Mayu; Shiraha, Keisuke; Matsuoka, Suzuka; Mitsumune, Sho; Nishimura, Jun; Watanabe, Hiromi; Kudo, Kenichiro; Fujiwara, Keiichi (Journal of Thoracic Disease, 2026)
Background: Cryobiopsy method using direct specimen retrieval through the working channel of the bronchoscope has recently been reported as a diagnostic option. However, its feasibility using an ultrathin bronchoscope (UTB) with 1.7-mm working channel has not been investigated. The aim of this study was to evaluate the feasibility, diagnostic yield, specimen size, and safety of direct cryobiopsy specimen retrieval through the 1.7-mm working channel of an UTB.Methods: We retrospectively reviewed patients with peripheral lesions who underwent cryobiopsy with direct specimen retrieval through the working channel using an UTB at National Hospital Organization (NHO) Okayama Medical Center between November 2022 and December 2025. We compared specimens obtained by cryobiopsy and small forceps biopsy. Diagnostic yield, and procedural safety were also evaluated.Results: Eighteen patients were included. We evaluated 53 cryobiopsy specimens and 18 forceps biopsy specimens. The median lesion diameter was 13.5 mm (range, 10–28 mm). Cryobiopsy specimens were significantly larger than forceps specimens (1.97 vs. 1.00 mm2, P